Flame structures and ignition characteristics of torrefied and raw sewage sludge particles at rapid heating rates - Mock, Chinsung; Lee, Hookyung; Choi, Sangmin; Manovic, Vasilije (Elsevier, 2017)
Torrefaction is a promising method for improving the quality of pulverised solid fuel, as it increases the flame stability, radiative heat transfer and energy density of the fuel. Raw sewage sludge contains less fixed carbon and more ash compounds than other biomasses; consequently, it has poor energy quality with a long ignition delay and forms a relatively low, sooty flame. In this study, we directly investigate the combustion behaviours of particles with varying degrees of torrefaction by burning them at 1340 K. The torrefied particles were prepared at different temperatures (473 K or 573 K) for different residence times (10 min or 30 min). The experimental parameters examined were the size range of the particles (150–215 μm and 255–300 μm) and the O2 percentage (10–40%). The particles were entrained from a cold carrier gas into a hot gas stream, igniting a volatile flame that was extinguished a few milliseconds later. These temporal variations in the burning particles were detected by in-situ high-speed photography (7000 frames/s). The torrefaction degree affected the flame structure and varied the ignition delay, due to the mismatched reactivity and soot formation at rapid heating rates. The most torrefied sludge particles exhibited a relatively luminous volatile cloud and a large flame, while preserving the duration of volatile combustion. These observations confirm the improved pulverised combustion of the torrefied sludge particles. We also obtained valuable flame parameters (radius, intensity and combustion time) of the differently torrefied sludge particles.
Keywords: Torrefaction; Sewage sludge; Volatiles; Ignition; Combustion; Flame